Links between macrophages in perivascular adipose tissue and arterial wall: a role in atherosclerosis initiation - Bartuskova, Hana; Kauerova, Sona; Petras, Marek; Poledne, Rudolf; Fronek, Jiri; Janousek, Libor; Kralova Lesna, Ivana (International angiology, 2022)
BACKGROUND: Inflammation of adipose tissue in relation to atherosclerosis is currently widely studied in patients with advanced disease. However, data regarding polarization of adipose tissue and arterial wall macrophages and their mutual link in the early stages of atherosclerosis are scarce. The main aim of this cross-sectional study was to characterize macrophage subpopulations in arterial wall and adjacent adipose tissue; and to determine links between different subpopulations in a relatively healthy population living kidney donors. METHODS: The presence of cardiovascular risk factors was established in 68 living kidney donors. Macrophage polarization was analyzed by flow cytometry and confirmed by RT-PCR in samples of visceral adipose tissue, renal artery and adjacent perivascular adipose tissue collected during hand-assisted retroperitoneoscopic nephrectomy. RESULTS: CD14+CD16+CD36high macrophages were found only in adipose tissues and were strongly positively associated with several cardiovascular risk factors. The CD14+CD16+CD36low subpopulation was positively associated with the presence of several cardiovascular risk factors to a lesser extent in all studied tissues. In contrast, the proportion of CD14+CD16-CD36low macrophages was negatively linked to several cardiovascular risk factors and increased in subjects on statin therapy. The proportion of CD14+CD16+CD36low macrophages in perivascular, not visceral adipose tissue was associated with that of both macrophage subtypes in the arterial wall, suggesting a direct link between perivascular adipose tissue and the arterial wall. CONCLUSIONS: We confirmed the association of three macrophage subtypes in adipose tissue and arterial wall to the studied cardiovascular risk factors. Macrophage polarization in perivascular, but not visceral adipose tissue was linked to macrophage polarization in the arterial wall.
Keywords: Hydroxymethylglutaryl-CoA Reductase Inhibitors; Macrophages; statiny; průřezové studie; lidé; makrofágy; Cross-Sectional Studies; tuková tkáň; ateroskleróza; Humans; Atherosclerosis; Adipose Tissue